PENGARUH PRICE BOOK VALUE, PRICE EARNING RATIO, DAN DIVIDEND YIELD TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2008-2010 (Students' Journal of Accounting and Banking, 2013)
This research aim to analyze influence of Price Book Value, Price Earning Ratio and Dividend Yield to Stock Return by partial in Indonesian Stock Exchange. Population in this research [is] manufacturing business which have been noted in Effect Exchange Indonesia till year period 2010. Research Sample with criterion which have been determined to be to be obtained by counted 14 manufacturing business which is go public in Indonesian Stock Exchange during 3 year, so that processed by data counted 42 data. Result of examination in obtaining that there is influence which significant and is positive of PBV to Stock Return by partial, there no influence which significant PER to Stock Return by partial, and there no influence which Dividend Yield significant to Stock Return by partial. Keywords: Price Book Value, Price Earning Ratio, Dividend Yield and Stock Return